Electrodeposited Cu–Pd bimetallic catalysts for the selective electroreduction of CO2 to ethylene. Issue 21 (19th October 2020) - Feng, Ruting; Zhu, Qinggong; Chu, Mengen; Jia, Shuaiqiang; Zhai, Jianxin; Wu, Haihong; Wu, Peng; Han, Buxing
Abstract : Cu–Pd bimetallic catalysts were fabricated on carbon paper (CP) by the electrodeposition method via a dynamic hydrogen bubble template approach. Abstract : Cu–Pd bimetallic catalysts were fabricated on carbon paper (CP) by the electrodeposition method via a dynamic hydrogen bubble template approach. At a potential of −1.2 V vs . RHE, the Faradaic efficiency (FE) of C2 H4 could reach 45.2% with a current density of 17.4 mA cm −2 in an H-type electrolytic cell. Detailed studies suggest that the enhanced performance of Cu–Pd/CP was attributed mainly to the synergistic effect, low interfacial charge transfer resistance, and the 3D architecture of the catalysts.